2017
DOI: 10.5205/1981-8963-v11i12a23068p5066-5073-2017
|View full text |Cite
|
Sign up to set email alerts
|

O idoso e a mobilidade urbana: uma abordagem reflexiva para a enfermagem

Abstract: Objective: to analyze the nursing performance in the attention to the elderly people in the face of urban mobility. Method: this is a qualitative, descriptive, reflexive analysis type, based on the review of the narrative literature with the discussion of the following points: the elderly people and urban mobility, the focus of accessibility to the elderly people before urban mobility and nursing care for the elderly urban mobility. Results: it is the responsibility of the nurse to make an active search assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
0
2
4
Order By: Relevance
“…However, for the population participating in this study, the increase in functional balance and mobility was not enough to decrease the fear of falling, which goes against the results obtained by other studies of a similar character, such as the one by Camacho and Gomes (2017) [15]. It can be suggested that, because the training took place in a virtual indoor environment, and the episodes of falls pointed out by the research participants were the home environment and around it, it did not generate significant security to have a decrease in this fear of falling [15,17]. In addition, the major cause of falls recorded in the study was tripping and slipping, these are situations arising from walking.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…However, for the population participating in this study, the increase in functional balance and mobility was not enough to decrease the fear of falling, which goes against the results obtained by other studies of a similar character, such as the one by Camacho and Gomes (2017) [15]. It can be suggested that, because the training took place in a virtual indoor environment, and the episodes of falls pointed out by the research participants were the home environment and around it, it did not generate significant security to have a decrease in this fear of falling [15,17]. In addition, the major cause of falls recorded in the study was tripping and slipping, these are situations arising from walking.…”
Section: Discussioncontrasting
confidence: 85%
“…The discontinuation of the sidewalks, the unevenness, the presence of holes and inadequate lighting, characterize factors of high risk for the elderly. It is noteworthy that these people have a progression of loss of functional capacities, presence of less muscle mass, a greater number of associated morbidities, leading to a worse functional state to face these existing extrinsic factors [14,15]. The balance optimization found in this study is corroborated by other studies that also investigated the influence of VR on the components of postural control [16,17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…En México, 34.1% de las personas de la tercera edad es económicamente activo (INEGI, 2018) y su principal ingreso proviene del trabajo por cuenta propia (CEPAL y OIT, 2018); por tanto, son personas independientes y la movilidad es un aspecto importante para ellos, pues requieren trasladarse a lugares de trabajo. La eficiencia de los servicios es esencial para que la función de la movilidad sea cálida y accesible, es decir, apropiada a las necesidades de las personas de la tercera edad mediante la adaptación y la modificación de la infraestructura y servicios de transporte (Camacho y Araújo-Gomes, 2017).…”
Section: Envejecimiento Y Movilidadunclassified
“…Además, desde la perspectiva de los ACS, los elementos que cruzan los aspectos psicosociales, que se encuentran en la vida cotidiana, adquieren una gran proporción en la génesis de las caídas. En otras palabras, para los ACS, los factores descritos que forman los comportamientos de riesgo son puntos clave para la prevención de caídas porque forman parte de la experiencia diaria de los mayores (3,34).…”
Section: Factores Psicológicosunclassified